Pengaruh Investment Opportunity Set, Ukuran Perusahaan, Dan Pertumbuhan Perusahaan Terhadap Nilai Perusahaan Manufaktur Sektor Industri Barang Konsumsi Yang Terdaftar Di Bei (Tahun 2019-2021) - Clarisa Gita Dewi; I Gusti Ayu Purnamawati (Universitas Pendidikan Ganesha, 2024)
This research aims to examine the influence of investment opportunity set, company size, and company growth partially and simultaneously on the value of manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2019-2021. This research uses quantitative methods. This research uses secondary data. The number of samples used was 60. The samples in this study analyzed the data using SPSS version 25. The data analysis techniques used in this research included: Descriptive statistical analysis, then carrying out classical assumption tests in the form of normality tests, multicollinearity tests, heteroscedasticity tests, and autocorrelation. The results obtained from this research are: (1) Investment Opportunity Set (X1) has a positive effect on Company Value (Y); (2) Company size (X2) has a positive effect on company value (Y); (3) Company Growth (X3) has a positive effect on Company Value (Y); (4) Investment Opportunity Set (X1), Company Size (X2), and Company Growth (X3) have a positive effect on Company Value (Y)